A clinical trial: Aqualizer ™ therapy and its effects on myopathies or temporomandibular dysfunctions. Part II: Subjective parameters - Buchbender, Mayte; Keplinger, Lukas; Kesting, Marco Rainer; Adler, Werner; Schmitt, Christian (Cranio-The Journal of Craniomandibular Practice, 2021)
Objective: Temporomandibular dysfunction (TMD) reduces patients’ quality of life (QoL). The aim was to assess the effects of initial Aqualizer™ therapy. Methods: Group 1 (initial Aqualizer™ therapy) before definitive splint therapy or Group 2 (no initial therapy). Patients with arthrosis, partial/total prosthesis, or were undergoing splint therapy were excluded. Subjective parameters were evaluated: duration and intensity of pain, influence on wellbeing, changes in the head/neck area, handling and improvement of the Aqualizer™, improvement in QoL. The statistical significance level was 5% (p < 0.05). Results: In 53 patients (Group 1 n = 25; Group 2 n = 28), the improvement in patients’ well-being and intensity of pain in both groups was significant (p < 0.001). An improvement in QoL was found in 84% of patients in Group 1 and 75% in Group 2. Conclusion: Initial Aqualizer™ therapy can decrease the intensity of pain and increase patients’.
CRIS-Team Scopus Importer:2021-02-26
Keywords: Aqualizer splint; headache; myofascial; pain; TMD/TMJ

A clinical trial: Aqualizer ™ therapy and its effects on myopathies or temporomandibular dysfunctions. Part I: Objective parameters. - Buchbender, Mayte; Keplinger, Lukas; Kesting, Marco Rainer; Adler, Werner; Schmitt, Christian (Cranio-The Journal of Craniomandibular Practice, 2024)
OBJECTIVE: Symptoms of temporomandibular dysfunction (TMD) may include pain in the muscles or restrictions opening the mouth. The aim of this study was to assess the effects of initial Aqualizer™ therapy. METHODS: Group 1 received initial Aqualizer™ therapy before definitive hard splint; Group 2 received no initial therapy. Patients with arthrosis, partial/total prosthesis or undergoing splint therapy were excluded. Objective (temporomandibular joint palpation, temporomandibular joint auscultation, palpation of the chewing muscles, and mobility of the lower jaw) parameters were evaluated. The level of statistical significance was 5% (p < 0.05). RESULTS: In 53 patients (Group 1 n = 25; Group 2 n = 28), a significant improvement (p < 0.001) was found in Group 1 in pain on palpation (masseter muscle, temporal muscle, post-mandibular region, lateral pterygoid muscle, and suboccipital region), but no significant differences in jaw mobility were found. CONCLUSION: Aqualizer™ therapy produces significant improvement of primary symptoms.
EVALuna2:465271

Anorganic bovine bone (ABB) vs. autologous bone (AB) plus ABB in maxillary sinus grafting. A prospective non-randomized clinical and histomorphometrical trial - Schmitt, Christian; Moest, Tobias; Lutz, Rainer; Neukam, Friedrich Wilhelm; Schlegel, Karl Andreas (Clinical Oral Implants Research, 2015)
This investigation focused on histological characteristics and 5-year implant survival after sinus floor augmentation with anorganic bovine bone (ABB, Bio-Oss(®) ) and ABB plus autologous bone (AB) with a ratio of 1/1.Nineteen consecutive patients with bony atrophy of the posterior edentulous maxilla and a vertical bone height <=4 mm were prospectively included in this study. In the first surgical stage, the maxillary sinus was non-randomized either augmented with ABB alone (n = 12) or a 1/1 mixture of ABB and AB (n = 7). After a mean healing period of 167 days, biopsies were harvested in the region of the grafted sinus with a trephine burr and implants were placed simultaneously, ABB n = 18 and ABB + AB n = 12. The samples were microradiographically and histomorphometrically analyzed judging the newly formed bone (bone volume, BV), residual bone substitute material volume (BSMV), and intertrabecular volume (soft tissue volume, ITV) in the region of the augmented maxillary sinus. Implant survival was retrospectively evaluated from patient's records.No significant difference in residual bone substitute material (BSMV) in the ABB group (31.21 ± 7.74%) and the group with the mixture of ABB and AB (28.41 ± 8.43%) was histomorphologically determined. Concerning the de novo bone formation, also both groups showed statistically insignificant outcomes; ABB 26.02 ± 5.23% and ABB + AB 27.50 ± 6.31%. In all cases, implants were installed in the augmented sites with sufficient primary stability. After a mean time in function of 5 years and 2 months, implant survival was 93.75% in the ABB and 92.86% in the ABB + AB group with no statistically significant differences.The usage of ABB plus AB to a 1/1 ratio leads to an amount of newly formed bone comparable with the solitary use of ABB after grafting of the maxillary sinus. Considering that ABB is a non-resorbable bone substitute, it can be hypothesized that this leads to stable bone over time and long-term implant success. Importantly, in the sole use of ABB, bone grafting and therefore donor site morbidities can be avoided.
EVALuna2:24380

A Retrospective Data Analysis for the Risk Evaluation of the Development of Drug-Associated Jaw Necrosis through Dentoalveolar Interventions - Buchbender, Mayte; Bauerschmitz, Charlotte; Pirkl, Sebastian; Kesting, Marco Rainer; Schmitt, Christian (International Journal of Environmental Research and Public Health, 2022)
This study aimed to analyse the development of medication-related osteonecrosis of the jaw (MRONJ) in patients who underwent surgical intervention to identify potential risk factors between three different groups sorted by the type of oral surgery (single tooth extraction, multiple extraction, osteotomy). Data from patients with this medical history between 2010 and 2017 were retrospectively analysed. The following parameters were collected: sex, age, medical status, surgical intervention location of dentoalveolar intervention and form of medication. A total of 115 patients fulfilled the criteria and underwent 115 dental surgical interventions (female n = 90, male n = 25). In total, 73 (63.47%) of them had metastatic underlying diseases, and 42 (36.52%) had osteoporotic ones. MRONJ occurred in 10 patients (8.70%) (female n = 5, male n = 5). The occurrence of MRONJ was significantly correlated (p ≤ 0.05) with the mandible site and male sex. Tooth removal at the mandible site remains the main risk factor for the development of MRONJ. The risk profile of developing MRONJ after dentoalveolar interventions could be expected as follows: tooth osteotomy > multiple extractions > single tooth extraction.
CRIS-Team Scopus Importer:2022-04-15
Keywords: antiresorptive therapy; MRONJ; oral surgery; risk profile

Bio-Oss® blocks combined with BMP-2 and VEGF for the regeneration of bony defects and vertical augmentation - Schmitt, Christian; Lutz, Rainer; Döring, Hendrik; Lell, Michael; Ratky, Jozsef; Schlegel, Karl Andreas (Clinical Oral Implants Research, 2013)
Objectives: The aim of this study was to evaluate the bone formation rate and osseointegration of Bio-Oss® blocks combined with rhBMP-2 and rhVEGF in bony defects and after vertical augmentation. Material and methods: Bio-Oss® blocks plus rhBMP-2 (BMP), Bio-Oss® blocks plus rhVEGF (VEGF), or Bio-Oss® blocks plus rhBMP-2 and rhVEGF (BMPVEGF) were inserted in "critical size defects" (CSD) in the calvariae of adult pigs. Control defects were filled with collagen carrier (Lyostypt®) plus growth factors and untreated Bio-Oss® blocks (CO). In a second group, Bio-Oss® blocks plus growth factors and untreated Bio-Oss® blocks were used for vertical augmentation of the calvariae. In the first group, the investigation time was 30 days, in the second group it was 30 and 60 days. The bone samples were investigated histomorphometrically, and the newly formed bone (BV/TV) was judged by microradiographic investigation. Results: In the CSD model, the newly formed bone in the region of interest was not significantly different within the groups. In the second setting, the inserted bone blocks exhibited sufficient volume stability with increasing bone formation up to 9.33% ± 3.92% for BMP, 10.42% ± 1.81% for BMP/VEGF, 11.01% ± 4.78% for VEGF, and 10.02% ± 5.43% for the control group after 60 days. Conclusion: In the chosen setting and time frame, de novo bone formation did not increase with the additional use of growth factors.
CRIS-Team Scopus Importer:2024-05-13
Keywords: Animal experiments; Biomaterials; Bone implant interactions; Bone regeneration; Bone substitutes; Growth factors; Guided tissue regeneration

Collagen Matrix Vascularization in a Peri-Implant Vestibuloplasty Situation Proceeds Within the First Postoperative Week - Preidl, Raimund; Wehrhan, Falk; Weber, Manuel; Neukam, Friedrich Wilhelm; Kesting, Marco Rainer; Schmitt, Christian (Journal of Oral and Maxillofacial Surgery, 2019)
Purpose: Vestibuloplasty is a frequently performed surgical procedure to create or increase soft tissue mucosal sealing around dental restorations. Collagen matrices have exhibited comparable clinical results as free gingival grafts in the context of intraoral tissue augmentation. However, the process of matrix vascularization, the basic requirement for local healing, is incompletely understood. Therefore, this study investigated collagen matrix perfusion in a clinical intraoral setting. Materials and Methods: In a prospective cohort study, vestibuloplasty was performed during implant exposure using prefabricated collagen matrices. Matric perfusion was determined intraoperatively and at days 2, 5, 7, 14, 30, and 90 using a laser Doppler spectrophotometer measuring oxygen saturation, relative amount of hemoglobin, blood flow, and blood velocity as primary outcome variables. These parameters were compared with perfusion of the oral mucosa surrounding the matrices. Statistical analysis was performed by applying variance and regression models. Results: In 10 patients (average age, 60.9 yr), vestibuloplasty was performed exclusively in the anterior mandible. Blood flow and tissue oxygen saturation in the augmented zones markedly increased until postoperative day 5 and approximated perfusion values of the adjacent mucosa at the following 2 time points. Likewise, matrix oxygen saturation markedly increased until day 7 and subsequently converged to perfusion parameters of the surrounding mucosa at the following time points. Conclusion: Flow signals in incorporated collagen matrices occurred on day 2 after vestibuloplasty and further increased until days 5 to 7. Therefore, matrix perfusion mainly occurs within the first postoperative week, converging to perfusion levels of the surrounding mucosa with minimal alterations during the following course.
CRIS-Team Scopus Importer:2019-05-09

Complications in external sinus floor augmentation: A literature overview - Schlegel, Karl Andreas; Hoehmann, Benedikt; Schmitt, Christian (Implantologie, 2018)
The posterior segment of the edentulous region represents an anatomical peculiarity when planning for the restoration of missing teeth with dental implants. Alveolar atrophy and pneumatization of the maxillary sinus often preclude the insertion of implants at standard lengths (> 8 mm). In cases of advanced atrophy and a residual bone height of less than 4 mm, it may also be impossible to place short implants (4 to 6 mm). In such cases, augmentation of the maxillary sinus (sinus elevation) is a predictable procedure to generate sufficient bone height for the insertion of dental implants. Depending on the residual bone height of the alveolar ridge, the anatomical conditions, and the planned restorative protocol, sinus elevation can be performed simultaneously with implant insertion (single-stage approach) or prior to implant insertion (two-stage approach). The main techniques for increasing the vertical bone height of the posterior maxilla are the transalveolar (internal) and lateral (external) sinus augmentation procedures. Both techniques have a high success rate. However, complications can arise during or after sinus elevation, and practitioners must be aware of how to address them. This article summarizes the most common complications in external sinus floor augmentation and discusses their prevention and management.
EVALuna2:35695

Corrigendum to "The influence of different abutment materials on tissue regeneration after surgical treatment of peri-implantitis - A randomized controlled preclinical study" [J Cranio-Maxillo-Facial Surg 45 (2017) 1190-1196] - Moest, Tobias; Wrede, Jan; Schmitt, Christian; Stamp, Melanie; Neukam, Friedrich Wilhelm; Schlegel, Andreas (Journal of Cranio-Maxillofacial Surgery, 2017)
EVALuna2:24445

Das freie Schleimhauttransplantat und dessen Alternativen - Schmitt, Christian (Implantologie, 2023)
Procedures to widen the peri-implant keratinized mucosa are often indicated in the context of implanttreatment. The aim is to generate a sufficient band of keratinized attached tissue (>2 mm) in the area where the implant passes through the oral mucosa. Attached keratinized soft tissue seems to have protective properties to avoid peri-implant infections. With soft-tissue transposition in the area of the implant at the time of implant exposure, the desired goal can often be achieved. However, if the tissue structures for transposition are insufficient, an apically positioned flap in combination with a free gingival graft is the gold standard of care. Nowadays, collagen matrices are available as an alternative to autologous tissue, which are used in the “open healing situation”. This article explicitly aims to discuss the clinical use of these matrices as an alternative to autogenic free-gingival grafts.
CRIS-Team Scopus Importer:2024-12-16
Keywords: collagen matrix; dental implant; free gingival graft; keratinized mucosa; soft-tissue substitute; vestibuloplasty

Diagnosis, avoidance and management of complications of implant-based treatments - Lutz, Rainer; Schmitt, Christian; Buchbender, Mayte; Neukam, Friedrich Wilhelm (European Journal of Oral Implantology, 2018)
This review provides an overview of review and consensus articles of the past 5 years regarding surgical complications in implant dentistry. The focus in this article is on surgical complications occurring after implant insertion and on risk factors that compromise oral implant osseointegration.
EVALuna2:35697

Evaluation of Staff Satisfaction After Implementation of a Surgical Safety Checklist in the Ambulatory of an Oral and Maxillofacial Surgery Department and its Impact on Patient Safety - Schmitt, Christian; Buchbender, Mayte; Musazada, Saida; Bergauer, Bastian; Neukam, Friedrich Wilhelm (Journal of Oral and Maxillofacial Surgery, 2018)
Purpose: Safety checklists in medicine have been shown to be effective in the prevention of complications and adverse events in patients undergoing surgery. Such checklists are not as common in dentistry. The aims of this study were to propose a safety checklist for the ambulatory treatment of patients undergoing oral and implant surgery and to assess its impact on patient safety and staff satisfaction. Materials and Methods: After implementation of a surgical safety checklist in the ambulatory treatment of patients undergoing oral and implant surgeries, a questionnaire regarding staff satisfaction and safety-related parameters was randomly administered. Incidents, complications, and adverse events were documented. Outcomes with (n = 40 surgeries) and without (n = 40 surgeries) use of the checklist were analyzed and compared. Results: Staff reported high satisfaction with the use of the checklist, which demonstrably improved team communication and lowered stress levels during surgery. There was a statistically significantly higher frequency of reported incidents without the use of the checklist (n = 43) than with the use of the checklist (n = 10; P =.000). Most incidents were reported in the context of pre- and post-procedural processes. Conclusions: Safety checklists help to improve work processes, optimize communication, and lower stress levels. Their use in clinical dental practice is recommended. (C) 2018 American Association of Oral and Maxillofacial Surgeons
EVALuna2:35086

Free Gingival Graft and Collagen Matrix Revascularization in an Enoral Open Wound Situation - Preidl, Raimund; Reichert, Sky Helen; Vallenas Coronel, Talisa; Kesting, Marco Rainer; Wehrhan, Falk; Schmitt, Christian (Journal of Oral and Maxillofacial Surgery, 2021)
Purpose: Vestibuloplasty with free gingival grafting is a frequently performed surgical procedure to generate sufficient keratinized mucosa (KM) around dental implants. Avascular porcine collagen matrices (CM) have been proclaimed to be sufficient substitutes as alternatives to free gingival grafts (FGGs). However, the process of graft integration and vascularization is still incompletely understood. Methods: In 18 patients a vestibuloplasty in the lower edentulous jaw situation was performed during implant exposure, either with FGGs from the palate or a porcine CM (mucoderm). Tissue perfusion of the soft tissue grafts was measured using laser-doppler-spectrophotometer intraoperatively and on postoperative days 2, 5, 10, 30 and between days 60 and 90. With graft perfusion expressed by oxygen saturation [SO2%], the relative amount of hemoglobin [rHb], blood flow, and velocity [AU] was detected and compared between groups and the surrounding mucosa. Results: Healing was uneventful in both groups, with mature KM around dental implants after healing. Blood flow and velocity significantly increased until postoperative day 10, comparable to perfusion values of the surrounded mucosa. Intergroup comparisons revelated no significant differences concerning the flow between CM and FGGs. Oxygen saturation also significantly increased within the first 5 postoperative days in both groups. Hemoglobin content did not show any differences during the investigated period. Conclusions: The perfusion mainly progresses within the first postoperative week with only minimal further detectable alterations until the final investigation, comparable in both groups. Although integration of FGGs (revascularized) and the CM (new tissue formation) is biologically different, both transplants show comparable perfusion patterns, leading to sufficient KM.
CRIS-Team Scopus Importer:2021-04-19

Hartgewebeaugmentationen: Materialwahl - Schlegel, Karl Andreas; Wiltfang, Jörg; Lutz, Rainer; Schmitt, Christian; Möst, Tobias (Implantologie, 2016)
Long-term dental implant success depends on bone quality and quantity. Insufficient bone quantity makes pre- or intraoperative augmentative procedures necessary. For this purpose, autologous, allogeneic, xenogeneic, and alloplastic bone substitute materials (BSMs) are available, which differ in their capacity for osteogenesis, osteoconduction, and osteoinduction. Due to superior regenerative potential, autologous bone grafts represent the gold-standard. However, since autologous bone grafting is associated with increased patient morbidity, non-autologous BSMs are increasingly applied in implantology. Appropriate material selection, treatment planning, and application of patient considerations requires knowledge of the characteristics of the selected BSMs.
CRIS-Team Scopus Importer:2024-05-13
Keywords: Allograft; Autograft; Bone substitute material (BSM); Grafting- procedures; Xenograft

Histological results after maxillary sinus augmentation with Straumann® BoneCeramic, Bio-Oss®, Puros®, and autologous bone. A randomized controlled clinical trial - Schmitt, Christian; Döring, Hendrik; Schmidt, Thomas; Lutz, Rainer; Neukam, Friedrich Wilhelm; Schlegel, Karl Andreas (Clinical Oral Implants Research, 2013)
Objective: This investigation focused on a comparison of clinical and histological characteristics after sinus floor augmentation with biphasic calcium phosphate (BCP, Straumann BoneCeramic®), anorganic bovine bone (ABB, Geistlich Bio-Oss®), mineralized cancellous bone allograft (MCBA, Zimmer Puros®), or autologous bone (AB). Materials and methods: Thirty consecutive patients with a posterior edentulous maxillary situation and a vertical bone height less than or equal to 4 mm were included in this study. A two-stage procedure was carried out. After augmentation of the maxillary sinus with ABB, BCP, MCBA, or AB followed by a healing period of 5 months, biopsies were taken with simultaneous implant placement. The samples were analyzed using microradiography and histology. Results: Ninety-four implants were placed in the augmented positions and 53 bone biopsies were taken and evaluated. The bone volume fraction of newly formed bone was measured as 30.28 ± 2.16% for BCP, 24.9 ± 5.67% for ABB, 41.74 ± 2.1% for AB, and 35.41 ± 2.78% for MCBA with significant increases in bone volume of AB vs. BCP and ABB, and MCBA vs. ABB samples. Significantly different residual bone substitute material was measured as 15.8 ± 2.1% in the BCP group and 21.36 ± 4.83% in the ABB group. Conclusion: As it provides the highest rate of de novo bone formation, AB can be considered to remain the gold standard in sinus floor augmentation. All tested control materials showed comparable results and are suitable for maxillary sinus augmentation.
CRIS-Team Scopus Importer:2024-05-13
Keywords: Biomaterials; Bone regeneration; Bone substitutes; Clinical research; Clinical trials; Guided tissue regeneration; Sinus floor elevation

Implants in the elderly patient - Schlegel, Karl Andreas; Schmitt, Christian; Möst, Tobias (Implantologie, 2020)
In our daily practice more and more patients show up who have received dental implants thirty or fourty years ahead. These patients are today related as "golden agers". At the same time in our days we can see that age related contraindications for implants are very liberal and no definite age limitation is valide any more. With some cases treated in the own office the reliability and problems of such aged patients should be highlighted. Also the question "quality of life" versus potential risks of these therapy options should be counterbalanced and at least when planning new implant borne rehablitations should be brought into consideration.
CRIS-Team WoS Importer:2021-02-05

Implants in the elderly patient Implantate beim hochbetagten patienten-Fluch oder segen?! fallserie hochbetagter patienten - Schlegel, Karl Andreas; Schmitt, Christian; Möst, Tobias (Implantologie, 2020)
In our daily practice more and more patients show up who have received dental implants thirty or fourty years ahead. These patients are today related as "golden agers". At the same time in our days we can see that age related contraindications for implants are very liberal and no definite age limitation is valide any more. With some cases treated in the own office the reliability and problems of such aged patients should be highlighted. Also the question "quality of life" versus potential risks of these therapy options should be counterbalanced and at least when planning new implant borne rehablitations should be brought into consideration.
CRIS-Team Scopus Importer:2020-07-31
Keywords: Age; Complications; Implants; Peri-implant mucositis; Peri-implantitis; Risk analysis

Increased malignancy of oral squamous cell carcinomas (oscc) is associated with macrophage polarization in regional lymph nodes - an immunohistochemical study - Wehrhan, Falk; Buettner-Herold, Maike; Hyckel, Peter; Moebius, Patrick; Preidl, Raimund; Distel, Luitpold; Ries, Jutta; Amann, Kerstin Ute; Schmitt, Christian; Neukam, Friedrich Wilhelm; Weber, Manuel (BMC Cancer, 2014)
It is largely accepted that specific immunological parameters in solid malignancies are associated with patient's prognosis. Recently a correlation of macrophage polarization with histomorphological parameters could also be shown in oral squamous cell carcinoma (oscc). The observed tumor derived peripheral immune tolerance could be associated with the macrophage polarization in regional tumor draining lymph nodes.So far there are no studies analyzing the macrophage polarization in cervical lymph nodes of oscc patients. In the present study we aimed to correlate macrophage polarization in different anatomical lymph node compartments of patients diagnosed with oscc with histopathologic parameters of the primary tumor (T-, N-, L-, V-, Pn-status, grading).Tumor free (n = 37) and metastatic (n = 17) lymph nodes of T1 and T2 oscc patients were processed for immunohistochemistry to detect CD68, CD11c, CD163 and MRC1 positive cells. Samples were digitized using whole slide imaging and the number of cells expressing the aforementioned markers in the region of interest quantitatively analyzed.The malignancy of the primary tumor (defined by T-, L-, Pn-status, grading) correlated with the lymph node macrophage polarization. L1 and Pn1 tumor cases displayed a significantly (p < 0.05) decreased M1 and increased M2 polarization in the sinus of the lymph nodes. G3 cases presented a significantly (p < 0.05) increased M2 polarization in the sinus compared to G2 cases. T2 tumors had significantly (p < 0.05) increased M2 polarization in the interfollicular zone of regional lymph nodes compared to T1 tumors. Metastatic and non-metastatic lymph nodes did not differ regarding their macrophage polarization.The current study revealed for the first time an influence of oscc on the macrophage polarization in regional lymph nodes. Markers of malignant behavior in the primary tumor were associated with a shift of macrophage polarization in lymph nodes from the anti-tumoral M1 type to the tumor-promoting M2 type. As tumor free and metastatic lymph nodes did not differ in terms of their macrophage polarization pattern, there must be other factors influencing the location for lymph node metastasis formation.
EVALuna2:18175

Investigation of the palatal soft tissue volume: a 3D virtual analysis for digital workflows and presurgical planning - Seidel, Anna; Schmitt, Christian; Matta, Ragai; Buchbender, Mayte; Wichmann, Manfred; Berger, Lara (BMC Oral Health, 2022)
BACKGROUND: In mucogingival and implant surgery, an autologous soft tissue graft from the palate is the gold standard for reconstructing missing keratinised soft tissue and volume. Previously, presurgical measurements of the graft harvesting site were described with two-dimensional (2D) linear measurements. The present observational clinical study aimed to evaluate a three-dimensional (3D) measurement method for determining the present palatal soft tissue volume for each patient individually. METHODS: Pre-existing cone beam computed tomography (CBCT) scans of 20 patients were converted into 3D Standard Tessellation Language models of the bone surface. Intraoral impressions of the maxilla were taken and digitised to visualise the gingival surface. The resulting virtual models of bone (reference value) and gingival (actual value) surfaces were merged, with tooth surfaces used for registration. The region between the central incisors and the hard palate was subdivided into 5 regions of interest (ROIs). The distance between palatal bone and gingival surface was analysed both volumetrically and linearly, and the results were statistically evaluated for the ROIs. RESULTS: The average gingival surface area on the palate was 19.1 cm2, and the mean volume was 58.2 cm3 (± 16.89). Among the ROIs, the mean linear value was highest in the most distal region, from the second molar to the hard palate (4.0 ± 1.09 mm) and lowest in the canine region (1.9 ± 0.63 mm). For mean distance, significant differences were found for the anterior palate and the most posterior palate in comparison with all other ROIs (p < 0.01). The volume measurements also declined significantly and steadily between the posterior (1.9 ± 1.0 cm3) and anterior palates (0.4 ± 0.2 cm3). CONCLUSIONS: By merging digital data, palatal soft tissue could be quantified virtually. The results were reliable and comparable to previous findings with linear measurement methods. This 3D soft tissue volume analysis method fully exploited the diagnostic potential of data that are frequently collected for presurgical planning in oral surgery (i.e., CBCT + surface scans). This evaluation method might be useful for volumetric and linear measurements in other applications in anatomy and for determining palatal soft tissue dimensions in the planning stage before surgical interventions. TRIAL REGISTRATION: This observational clinical trial was retrospectively registered in the German Clinical Trials Register, reference number: DRKS00023918.
CRIS-Team Scopus Importer:2022-09-02
Keywords: Cone-beam computed tomography; Connective tissue; Hard palate; Imaging; Maxilla; Oral surgical procedures; Reference values; Soft palate; Three-dimensional

In vivo evaluation of biofunctionalized implant surfaces with a synthetic peptide (P-15) and its impact on osseointegration. A preclinical animal study - Schmitt, Christian; Köpple, Markus; Moest, Tobias; Neumann, Konrad; Weisel, Tamara; Schlegel, Karl Andreas (Clinical Oral Implants Research, 2016)
The overall aim of the study was to investigate a biofunctionalized implant surface with electrochemically deposition of hydroxyapatite and the synthetic peptide (P-15) and its effect on osseointegration.Three modified implant types of ANKYLOS(®) C/X implants were used; (1) machined implants used as negative control (M, n = 20), (2) implants with the FRIADENT(®) plus surface (grit blasted and acid-etched) used as positive control (P, n = 20), and (3) implants with a biomimetic surface consisting of hydroxyapatite and the synthetic 15 aminoacids containing peptide P-15 (BP, n = 40). The implants were randomly inserted in the mandibles of 10 beagle dogs following 4 months after tooth extraction (P1-P4). Three animals were sacrificed 2 and 7 days after implant insertion, respectively, and four animals were sacrificed 6 months post implant insertion. Bone-to-implant contacts (BICs) were analyzed via histomorphometrical analyses at five different region of interests (ROIs); two at the middle part on either side of the implant (ROI 1/4), two at the apical part of the implant at each side (ROI 2/3), and one at the tip of the implant (ROI 5).All implant surfaces showed a high level of osseointegration and osteoconductivity. The cumulative implant survival rate (CSR) was 93.8%, 100% in the M, 85% in the P, and 95% in the BP group. No statistical difference in BICs at ROI 1/4, 2/3, and 5 could be shown between implant types following 2 and 7 days of healing. BIC values increased in all groups over time. After 6 months of healing the BP group showed superiority in BIC in ROI 2/3 (73.2 ± 15.6%) compared to the P (48.3 ± 10.6%) and M group (66.3 ± 30.2%) with a significant difference between BP and P (P = 0.002).It is hypothesized, that the surface biofunctionalization improves peri-implant bone formation and remodeling, leading to an increased bone-to implant contact. However, within the limitations of the study set-up no benefit in the early phase of osseointegration could be established for dental implants with P-15 containing surface in this study.
EVALuna2:24427

Is keratinized mucosa indispensable to maintain peri-implant health? A systematic review of the literature - Brito, Carlos; Tenenbaum, Howard C.; Wong, Benjamin K. C.; Schmitt, Christian; Nogueira-Filho, Getulio (Journal of Biomedical Materials Research Part B-Applied Biomaterials, 2014)
The significance of keratinized mucosa (KM) around dental implants is still not well explained and has been controversial. The aim of this systematic review was to evaluate the importance of KM around dental implants. The electronic databases Cochrane library, MEDLINE, EMBASE, and Virtual Health Library (VHL) databases were utilized to search original articles from 2006 to March 2013. The inclusion and exclusion criteria used to select the articles were: (1) Human studies published in the English language; (2) Study published in international peer-viewed journals; (3) Studies evaluated the association between KM width and the peri-implant tissue health; (4) Studies that have follow up of greater than 12 months; (5) Publication of studies not older than 10 years. The searches retrieved 285 citations. Seven articles fulfilled all of the inclusion criteria. Out of these, three studies were ranked as presenting high methodological quality, and four were judged to be of moderate quality. This systematic review concludes that the presence of an adequate zone of keratinized tissue may be necessary because it was shown to be related to better peri-implant tissue health. Further randomized controlled trials are necessary to support this statement. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 102B: 643-650, 2014.
EVALuna2:24315

Kobra surgery simulator—a possibility to improve digital teaching? A case-control study - Buchbender, Mayte; Maser, Mathias; Neukam, Friedrich Wilhelm; Kesting, Marco Rainer; Attia, Sameh; Schmitt, Christian (International Journal of Environmental Research and Public Health, 2021)
Computer-aided simulations have long been of great importance in university teaching; however, to date, there is limited use of such simulations in the dental surgical sector. For this purpose, an oral surgery simulator, “Kobra”, was implemented in student training and was evaluated for dental education. Dental students (group 1, third-year and group 2, fourth-year) and dentists of the faculty (control group) were trained to use the simulator. The outcomes for group 1 (apicoectomy of an upper lateral incisor with Kobra), group 2 (removal of an impacted lower wisdom tooth with Kobra) and the control group (both procedures with Kobra) were evaluated. For evaluation purposes, subjective parameters (improvement of practical skills, comparison between conventional training and Kobra simulation, and implementation of simulation-based teaching) and objective parameters (removal of bone, tooth substance and soft tissue measured while performing the Kobra simulation) were assessed using questionnaires with a scale ranging from 1–5. A total of 49 students (third-year n = 29, with 22 women and 7 men; fourth-year n = 20, with 17 women and 3 men) and 10 dentists (women n = 5 and men n = 5) participated. Compared to the Kobra simulation, the conventional training method with plastic models was still favored (the difference was non-significant). Compared to the dentists, the simulation data showed a less precise surgical performance of the students (the difference was not significant). The Kobra simulation may offer an additional method to conventional surgery training using plastic models, with benefits for students and faculty staff.
CRIS-Team Scopus Importer:2021-02-26
Keywords: Coronavirus; COVID-19; Oral surgery; Surgery simulator; Surgical skills

Long-term changes in graft height after maxillary sinus augmentation, onlay bone grafting, and combination of both techniques: a long-term retrospective cohort study - Schmitt, Christian; Karasholi, Tarek; Lutz, Rainer; Wiltfang, Joerg; Neukam, Friedrich Wilhelm; Schlegel, Karl Andreas (Clinical Oral Implants Research, 2014)
This investigation focused on long-term changes in graft height, implant survival rate, and peri-implant tissue conditions of dental implants placed in alveolar ridges after augmentation procedures with a follow-up of 10 years.We conducted a retrospective cohort study with prospective long-term follow-up of 25 patients with edentulous severe atrophic maxillary situations who received a vertical augmentation procedure with autologous bone prior to implant placement. The participants were divided into three groups according to whether they underwent sinus elevation, onlay grafting, or a combination of both techniques. After a four-month healing period, 127 implants were inserted in the corresponding regions. Following a six-month healing period, the participants underwent prosthodontic rehabilitation, incorporating a fixed or removable implant denture. The cohort was clinically and radiographically followed up 1, 5, and 10 years after augmentation. The following parameters were measured: radiographic vertical bone changes, implant loss, peri-implant pocket depth (PD), width of keratinized mucosa (KM), sulcus fluid flow rate (SFFR), and the radiographic distance between the implant shoulder and the first visible bone-to-implant contact (DIB).Seven implants were lost during the observation period, resulting in a cumulative 10-year survival rate of 94.48%. Significant bone loss occurred during the first 12 months, after which the resorption slowed down and bone height eventually stabilized. After 10 years, the total vertical bone loss was 27.51% after onlay grafting, 28.14% after sinus elevation, and 30.24% in the combination group, with no statistically significant between-group differences. Peri-implant follow-up examinations revealed a positive correlation between SFFR and PD, respectively, DIB, and a negative correlation between SFFR and KM.The treatment method does not seem to impact vertical bone loss following augmentation using autologous grafts. This approach results in long-term stability of dental implants. A sufficient width of keratinized peri-implant mucosa is important to prevent peri-implant bone loss and inflammation.
EVALuna2:24344

Long-Term Influence of Platelet-Rich Plasma (PRP) on Dental Implants after Maxillary Augmentation: Implant Survival and Success Rates - Attia, Sameh; Narberhaus, Clara; Schaaf, Heidrun; Streckbein, Philipp; Pons-Kuehnemann, Joern; Schmitt, Christian; Neukam, Friedrich Wilhelm; Howaldt, Hans-Peter; Boettger, Sebastian (Journal of Clinical Medicine, 2020)
The atrophic maxilla often requires bone augmentation before implant placement to ensure long-term implant success. A previous prospective clinical trial examined the use of platelet-rich plasma (PRP) during maxillary augmentation. The short-term results showed no positive effect of PRP. The aim of this study was to evaluate the same patient collective of the previous study regarding the PRP long-term impact on the survival and success of dental implants. Fifty-three patients from the previous study diagnosed with maxillary atrophy and augmented with autologous bone grafts from the iliac crest and dental implants, were included in this study. Treatment was carried out on both sides in 34 patients with a split-mouth-design in which one randomly chosen side was treated additionally with PRP, the other side was the control-side. Nineteen patients were treated only on one side and were assigned to the PRP-or the control group randomly. Implant follow-up of the patients from the previous study was performed after an average time of 13 years. Implant success was evaluated using two different success criteria. Thitry-seven patients (25 women and 12 men) were investigated in this study. Seventeen patients (12 female, 5 male) were included in the PRP group, while 20 patients (13 female, 7 male) participated in the control group. A total of 210 implants were inserted. Of these, 102 implants (48.57%) were placed in the PRP group and 108 implants (51.42%) in the control group. Out of 102 investigated implants in the PRP group, 6 were removed (survival rate 94.1%). While two of the 108 implants in the control group were loss (survival rate 98.1%). In the PRP group, the cumulative probability of survival after 15.1 years was 94.1% and in the control group, was 98.1%, with no significant difference between the two groups. Higher significant difference for the control group was found in the cumulative success probability using Albrektson criteria (p = 0.05). Positive impact of PRP on long-term implant survival and success could not be found.
CRIS-Team WoS Importer:2020-03-24

Long-Term Influence of Platelet-Rich Plasma (PRP) on Dental Implants after Maxillary Augmentation: Retrospective Clinical and Radiological Outcomes of a Randomized Controlled Clinical Trial - Attia, Sameh; Narberhaus, Clara; Schaaf, Heidrun; Streckbein, Philipp; Pons-Kuehnemann, Joern; Schmitt, Christian; Neukam, Friedrich Wilhelm; Howaldt, Hans-Peter; Boettger, Sebastian (Journal of Clinical Medicine, 2020)
The long-term clinical and radiological outcomes of dental implants inserted in augmented bone treated with platelet-rich plasma (PRP) has not been well addressed in the literature yet. This study is based on a collection of patients from a randomized controlled trial (RCT) that did not report any short-term positive effects of PRP on bone healing after sinus lift surgery using autologous iliac crest bone graft. This study aimed to evaluate the long-term impact of PRP regarding clinical and radiological outcomes on the inserted implants in the previous RCT. For this evaluation, we considered the following variables: plaque index, probing depth, bleeding index, mobility grade, Periotest((R)) values, and radiological bone loss. Out of 53 patients (n = 306 implants) included in the previous study we were able to reinvestigate 37 patients (n = 210 implants) in two centers (31 in Giessen, Germany and 6 in Erlangen, Germany). Clinical and radiographic parameters suggested overall healthy conditions of the peri-implant tissue. The PRP-group and the control group did not differ significantly in the majority of the parameters. The overall evaluation showed that result data of the PRP-group was inferior to the control group in 64 percent of the evaluated parameters. The present study cannot provide evidence of a positive effect of PRP on the long-term implant clinical and radiological outcomes. In fact, a tendency towards inferior long-term results in the PRP-group was detected without reaching a significant threshold. Further controlled trials need to be conducted to investigate this correlation.
CRIS-Team WoS Importer:2020-03-24

Oral implant survival in patients with bisphosphonate (BP)/antiresorptive and radiation therapy and their impact on osteonecrosis of the jaws. A systematic review - Schmitt, Christian; Buchbender, Mayte; Lutz, Rainer; Neukam, Friedrich Wilhelm (European Journal of Oral Implantology, 2018)
AIM: In this systematic review, we aimed to assess the impact of endosseous implants on the formation of an osteonecrosis of the jaw, as well as implant survival rates for patients under bisphosphonate (BP), antiresorptive and radiation therapy. MATERIALS AND METHODS: An electronic search was performed using PubMed, Embase, and Medline databases with the logical operators: "dental implant", "antiresorptive", "bisphosphonate", "irradiation", "radiotherapy", "radiation", "necrosis" and "survival". The search was limited to articles published up to 15 December 2016. Recent publications were also searched manually to find any relevant studies that might have been missed using the search criteria noted above. The outcome variables were the implant survival rate and the frequency of osteonecrosis of the jaws. RESULTS: In total, 18 studies addressing oral implants in patients with BP or antiresorptive therapy and 23 with radiation therapy met the inclusion criteria and were included in this systematic review. Most of the studies had a retrospective design with a level of evidence (LoE) of III (moderately high risk of bias). Implant survival rate ranged from 92.86% to 100% in patients with BP/antiresorptive therapy (all due to osteoporosis) and 38.5% to 97.9% in patients with radiation therapy. For BP patients, osteonecrosis in relation to oral implants more frequently occurred in patients taking BPs due to malignant diseases. In patients with radiation therapy, an "implant triggered" necrosis is also a potential complication. The lack of data in the current literature concerning this issue does not allow a proper risk assessment to date. CONCLUSIONS: Within the limits of this systematic review, implant treatment concepts seem to be a valuable approach in patients with radiation therapy and patients with BP therapy due to an osteoporosis. In patients taking BPs due to a malignant disease, implant treatments are not recommended due to the high number of reported implant-related necrosis in this patient cohort. Outcomes of this review should, however, be regarded with caution due to the low level of evidence of the currently existing data.
EVALuna2:35698

Osseous ingrowth in allogeneic bone blocks applied for vertical bone augmentation: a preclinical randomised controlled study - Möst, Tobias; Frabschka, Johanna; Kesting, Marco Rainer; Schmitt, Christian; Frohwitter, Gesche; Lutz, Rainer; Schlegel, Karl Andreas (Clinical Oral Investigations, 2019)
Objectives: The aim of the present study was the qualitative and quantitative evaluation of osseous graft consolidation using allogeneic bone blocks for vertical bone augmentation in an animal model. Material and methods: Standardised allogeneic and autologous bone blocks were fixed on the frontal skull of 20 adult female pigs and covered with a resorbable collagen membrane. Animals were sacrificed after 2 and 6 months. Specimens were histologically and histomorphometrically analysed focusing on the amount of vital bone, residual bone substitute material and connective tissue. Furthermore, the amount of expression of bone matrix proteins (collagen type I and osteocalcin) and de novo vessel formation (von Willebrand factor) were quantified by immunohistochemistry. Results: Significantly more allogeneic bone blocks failed for both evaluation time points (p < 0.05). Allogeneic blocks showed significantly less vital bone with more connective tissue formation compared to autologous bone blocks. Increased vessel formation could be detected for both evaluation time points in the contact area of autologous bone with local bone. The expression of collagen type I and osteocalcin was significantly lower in the allogeneic bone graft. Conclusions: Allogeneic cancellous bone blocks showed a significantly higher failure rate compared to autologous bone blocks. Allogeneic bone blocks seemed to negatively affect bone formation or negatively influence the host in the long term, and increased connective tissue formation and block loss should be anticipated. Clinical relevance: In order to maintain patient safety and treatment success clinicians should be persuaded to make a conscious choice of the applied biomaterials with regard to their components and structure.
CRIS-Team Scopus Importer:2019-12-27
Keywords: Allogeneic bone block; Animal model; Bone substitutes; Histomorphometry; Immunohistochemistry

Retrospective 3D analysis of bone regeneration after cystectomy of odontogenic cysts - Buchbender, Mayte; Koch, Birte; Kesting, Marco Rainer; Matta, Ragai; Adler, Werner; Seidel, Anna; Schmitt, Christian (Journal of X-Ray Science and Technology, 2020)
BACKGROUND/OBJECTIVE: In this retrospective study, we aimed to investigate a new 3D evaluation method for evaluating bone regeneration after cystectomy of odontogenic cysts. METHODS: The study included 26 patients who underwent cystectomies between 2012 and 2017 and had received either fillings or non-fillings with autologous iliac crest. Bony regeneration was analyzed using 3D imaging software and comparing identical regions of interest (ROIs) that were determined by exact overlays of the postoperative cone beam computer tomography (CBCT) or computer tomography (CT) images. Outcome measures, including volume changes according to the defect size and configuration, patient age, the entity and distribution of the cysts, were collected. RESULTS: Twenty-six patients (5 women and 21 men) had 30 defects, including nine keratocysts, seven radicular cysts and 14 dentigerous cysts. A total of 73% of the defects were in the mandible. The mean 3D follow-up time was 12 months. According to the 3D evaluation of bony regeneration, the defect size and configuration showed no significant differences between the groups (filled or non-filled with 15 defects per group). CONCLUSIONS: By establishing a standardized 3D method for evaluating bone regeneration, healing can be better monitored and evaluated.
CRIS-Team Scopus Importer:2020-12-25
Keywords: Autologous bone; cystectomy; defect filling; odontogenic cysts; three-dimensional methodology

The influence of different abutment materials on tissue regeneration after surgical treatment of peri-implantitis - a randomized controlled preclinical study - Moest, Tobias; Wrede, Jan; Schmitt, Christian; Stamp, Melanie; Neukam, Friedrich Wilhelm; Schlegel, Karl Andreas (Journal of Cranio-Maxillofacial Surgery, 2017)
This study aimed to assess the impact of different abutment materials on peri-implant tissue regeneration after surgical treatment of peri-implantitis in a large animal model.Titanium implants (n = 51) were inserted in the upper and lower jaw of eight beagle dogs and a peri-implant infection was induced. After two months the peri-implant infection was surgically treated and abutments with different surfaces (Ti-2: n = 14; CoCrMb: n = 13; Ag-modified Ti-4: n = 14; Ti-4 control: n = 10) were applied. Clinical attachment level (CAL), modified sulcus bleeding index (mBI), bleeding on probing (BoP), and the sulcus fluid flow rate (SFFR) were determined 4, 8, and 12 weeks after surgical treatment to document the peri-implant tissue reaction.Superior levels for CAL and mBI were found with the Ti-4 control and the Ag-modified abutments, with the Ag-modified abutments showing the best values after 12 weeks. Lowest SFFR values compared with the other treatment groups underlined the superior soft tissue reaction adjacent to Ag-modified abutments. After 12 weeks inferior CAL, SFFR, BOP and mBI values were documented for the Ti-2 surface.Within limitations of the study, Ag-modified abutments lead to superior tissue reactions. Further studies are needed to investigate the properties of abutment materials.
EVALuna2:24442

Three-dimensional assessment after maxillary sinus grafting with a bovine, a porcine, and a synthetic bone substitute material. A randomized controlled clinical trial. - Schmitt, Christian; Wiesheu, Simon; Schlegel, Karl Andreas; Adler, Werner; Kesting, Marco Rainer; Matta, Ragai; Möst, Tobias (International Journal of Computerized Dentistry, 2024)
AIM: The present randomized controlled clinical trial focused on graft volume alterations after sinus floor augmentation with a deproteinized bovine bone mineral (DBBM; Bio-Oss), a deproteinized porcine bone mineral (DPBM; THE Graft), or a biphasic calcium phosphate (BCP; Osopia) material. MATERIALS AND METHODS: A total of 28 patients with edentulism in the posterior maxilla with ≤ 5 mm of residual bone height received a two-staged external sinus grafting procedure with DBBM, DPBM, or BCP. Three CBCT scans were performed: 1) prior to surgery (CBCT1); 2) directly after surgery (CBCT2); 3) after a healing period of 4 to 6 months, prior to implant placement (CBCT3). The CBCT scans were used to analyze volumetric alterations of the sinus grafts by virtual 3D model matching of CBCT1 and CBCT2 (situation after sinus grafting), and CBCT1 and CBCT3 (situation prior to implant placement). RESULTS: The volume of the bone graft in the maxillary sinus (volume [VOL%] directly after grafting rated as 100%) was stable after the healing period in the DBBM (VOL%: 103 ± 4%) and the DPBM (VOL%: 112 ± 23%) groups, with no statistically significant differences regarding 3D measurements. In the BCP group, the grafted volume declined to VOL%: 66 ± 25%, statistically inferior to the DBBM and DPBM groups. CONCLUSIONS: Regarding bone graft stability/volume, the DBBM and DPBM groups showed comparable outcomes. Due to resorption, the BCP group showed inferior bone graft volume after healing (statistically significant) compared with the DBBM and DPBM groups.
EVALuna2:541030

Volumetric soft tissue alterations in the early healing phase after peri- implant soft tissue contour augmentation with a porcine collagen matrix versus the autologous connective tissue graft: A controlled clinical trial - Schmitt, Christian; Brueckbauer, Patrick; Schlegel, Karl A.; Buchbender, Mayte; Adler, Werner; Matta, Ragai (Journal of Clinical Periodontology, 2020)
Aim This study evaluates the early volumetric changes after buccal soft tissue contour augmentation around implants with a porcine collagen matrix (CM) vs. the subepithelial connective tissue graft (SCTG) from the palate.
CRIS-Team WoS Importer:2020-11-27